2018
DOI: 10.1108/ecam-09-2016-0205
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder complexity in large scale green building projects

Abstract: Purpose In response to the world’s rising awareness on sustainability, industry players and policymakers are devoting great efforts to bolster green building developments. Every green building project (GBP) involves numerous stakeholders and potentially incompatible concerns. Despite the associated environmental, economic and social benefits, GBP developments have often confronted managerial barriers which are actually emerged from stakeholders – the actual key determinants of a project. Holistically analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Their findings indicate that rent premiums and higher prices are generated in LEED certified properties. Additionally, green properties are absorbed by the market in less than half the time when compared to those without green certification [14]. The 2019 study that looked at the city of Hong Kong (7.5 m) by Wadu Mesthrige and Chan [15] found that developer and investor stakeholders were uncertain and sceptical about the financial rewards of green certification.…”
Section: Place-based Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings indicate that rent premiums and higher prices are generated in LEED certified properties. Additionally, green properties are absorbed by the market in less than half the time when compared to those without green certification [14]. The 2019 study that looked at the city of Hong Kong (7.5 m) by Wadu Mesthrige and Chan [15] found that developer and investor stakeholders were uncertain and sceptical about the financial rewards of green certification.…”
Section: Place-based Contextmentioning
confidence: 99%
“…Traditionally one of the major considerations is market valuation, expressed as the asking rent of office space per square foot. This study uses an approach used by similar studies that were conducted in Milan [14] and Hong Kong [16]. These studies use a hedonic model in the form of an ordinary least squares (OLS) linear regression model based on a fixed effects approach to the attributes of commercial office property on rental price.…”
Section: Stage One Reserch Designmentioning
confidence: 99%
“…e relationally defined method was more frequently adopted in Category III (11.90%). Two sampling methods, including snowball sampling [56,118,125] and chain-referral sampling [121,123], were used in these studies. Compared with Category III, the methodologically defined method was more frequently used in Categories I, II, and IV (27.03%, 31.25%, and 92.31%, resp.).…”
Section: Research Designsmentioning
confidence: 99%
“…The global challenges caused by global warming, rapid urbanization, economic instability, and the ever-reducing affordability of housing call for rethinking and improvement of the ways we design and construct new buildings and renovate the existing ones. Aiming to answer this call, the research agenda of "better buildings" has been expanding rapidly over the last several decades, resulting in the development of multiple research domains and themes such as green buildings [1][2][3][4], low-and zero-carbon buildings [5][6][7][8], passive buildings [9,10], sustainable buildings [11,12], circular buildings [13,14], resilient buildings [15,16], smart buildings [17,18], and healthy buildings [19,20]. Some of the themes have made their way to statutes, building codes, standards, and certification schemes and certain ideas have been adopted by practitioners but there is still a very long way to go if we want to meet present and future challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The project development and design processes in the construction industry are still often disconnected and based on individualistic principles where each involved party seeks to maximize their own local gains and optimize their own part of the project development chain, which can result in suboptimal performance on the project level [21,22]. With the increasing complexity of the projects and a greater number of internal and external stakeholders and perspectives involved, it will become harder to come to a consensus and that, as a consequence, could result in conflicts, project delays, and expanding project costs [4,[23][24][25][26]. Moving forward, the process will need to become more integrated, streamlined, and actively involve multiple stakeholders at all the stages of project development, starting from the earliest ones [21,25,27,28].…”
Section: Introductionmentioning
confidence: 99%